Model Komunikasi Korporat Sari Ater Hotel & Resort Dalam Menghadapi Revolusi Industri 4.0 - Poppy Ruliana; Puji Lestari; Susi Andrini (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
The importance of implementing the corporate communication model at Sari Ater Hotel & Resort in the face of the industrial revolution 4.0 is faced with the use of new media and the effects of these changes on the company. The purpose of this study was to find out and find the corporate communication model of Sari Ater Hotel & Resort. The study used descriptive qualitative method, where data was obtained through in-depth interviews (in-depth interviews) and observations of informants (Director of Sales, Marketing Manager, and Public Relations Manager). The results of this study indicate that the social media communication model for corporate Sari Ater Hotels & Resort is relevant because in reality digital media has an influence on the implementation of Public Relations activities R Sari Ater Hotel & Resort has even been used as a medium to interact with the public, both internal and external public because through the internet can be known various information and issues that are developing or changes that occur so that a PR practitioner Sari Ater Hotel & Resort can access all information required according to the needs of the organization. The research findings are interactional communication models that can be applied at Sari Ater Hotel & Resort in the face of a linear and circular 4.0 industrial revolution